Pengaruh Karakteristik Tujuan Anggaran Dan Struktur Desentralisasi Terhadap Kinerja Aparat Pemerintah Daerah (Studi Kasus Pada Dinas Pendapatan, Pengelolaan Keuangan Dan Aset Daerah Kabupaten Sukoharjo) - Tiana, Agustika, Dra. Mujiayati, M.Si (2016)
The purpose of this study was to analyze the Influence of Characteristics Purpose Decentralized Budget and Structural Performance Against Local Government Officials at the Department of Revenue, Finance and Asset Sukoharjo district. This study uses the entire population DPPKAD apparatus Sukoharjo totaling 47 people with sampling Convenience sampling technique. Number of questionnaires distributed by 47 and returning as many as 40. The sample in this study as many as 40 samples and processed using SPSS for hypothesis testing. The study found that participation Budget, Budget Targets Clarity, Feedback Budget, Evaluation of the Budget, Budget Difficulties Purpose, Structure and Decentralization simultaneously affect the performance of Local Government Officers seen from the distribution of F> Ftable is 33.049> 2.390. The independent variables in this study consists of Participation Budget, Budget Targets Clarity, Feedback Budget, Evaluation of the Budget, Budget Difficulties Purpose, Structure and Decentralization able to explain the variability of the dependent variable Performance of Local Government Officers of 83.1%, and the remaining 16.9% explained by other variables outside the study.